Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the value of \(\cos(A - B)\), we need to use the trigonometric identities and the given information about the angles.
Given:
- \(\sin (A) = \frac{4}{5}\) and \(\frac{\pi}{2} < A < \pi\)
- \(\sin (B) = \frac{-2 \sqrt{5}}{5}\) and \(\pi < B < \frac{3 \pi}{2}\)
Let's work through this step-by-step:
### Step 1: Determine \(\cos(A)\)
Since \(\frac{\pi}{2} < A < \pi\), angle \(A\) is in the second quadrant, where sine is positive and cosine is negative. We use the Pythagorean identity:
[tex]\[ \sin^2(A) + \cos^2(A) = 1 \][/tex]
Substituting the given value of \(\sin(A)\):
[tex]\[ \left(\frac{4}{5}\right)^2 + \cos^2(A) = 1 \][/tex]
[tex]\[ \frac{16}{25} + \cos^2(A) = 1 \][/tex]
[tex]\[ \cos^2(A) = 1 - \frac{16}{25} \][/tex]
[tex]\[ \cos^2(A) = \frac{25}{25} - \frac{16}{25} \][/tex]
[tex]\[ \cos^2(A) = \frac{9}{25} \][/tex]
[tex]\[ \cos(A) = \pm \frac{3}{5} \][/tex]
Since \(A\) is in the second quadrant, \(\cos(A)\) is negative:
[tex]\[ \cos(A) = -\frac{3}{5} \][/tex]
### Step 2: Determine \(\cos(B)\)
Since \(\pi < B < \frac{3 \pi}{2}\), angle \(B\) is in the third quadrant where both sine and cosine are negative. Again, we use the Pythagorean identity:
[tex]\[ \sin^2(B) + \cos^2(B) = 1 \][/tex]
Substituting the given value of \(\sin(B)\):
[tex]\[ \left(\frac{-2 \sqrt{5}}{5}\right)^2 + \cos^2(B) = 1 \][/tex]
[tex]\[ \frac{4 \cdot 5}{25} + \cos^2(B) = 1 \][/tex]
[tex]\[ \frac{20}{25} + \cos^2(B) = 1 \][/tex]
[tex]\[ \cos^2(B) = 1 - \frac{20}{25} \][/tex]
[tex]\[ \cos^2(B) = \frac{25}{25} - \frac{20}{25} \][/tex]
[tex]\[ \cos^2(B) = \frac{5}{25} \][/tex]
[tex]\[ \cos(B) = \pm \frac{\sqrt{5}}{5} \][/tex]
Since \(B\) is in the third quadrant, \(\cos(B)\) is negative:
[tex]\[ \cos(B) = -\frac{\sqrt{5}}{5} \][/tex]
### Step 3: Calculate \(\cos(A - B)\)
Now, we use the formula for \(\cos(A - B)\):
[tex]\[ \cos(A - B) = \cos(A)\cos(B) + \sin(A)\sin(B) \][/tex]
Substitute the known values:
[tex]\[ \cos(A - B) = \left(-\frac{3}{5}\right)\left(-\frac{\sqrt{5}}{5}\right) + \left(\frac{4}{5}\right)\left(\frac{-2 \sqrt{5}}{5}\right) \][/tex]
[tex]\[ \cos(A - B) = \frac{3 \sqrt{5}}{25} + \frac{-8 \sqrt{5}}{25} \][/tex]
[tex]\[ \cos(A - B) = \frac{3 \sqrt{5} - 8 \sqrt{5}}{25} \][/tex]
[tex]\[ \cos(A - B) = \frac{-5 \sqrt{5}}{25} \][/tex]
[tex]\[ \cos(A - B) = -\frac{\sqrt{5}}{5} \][/tex]
Thus, the value of \(\cos(A - B)\) is \(-\frac{\sqrt{5}}{5}\).
So, the correct answer is:
[tex]\[ \boxed{-\frac{\sqrt{5}}{5}} \][/tex]
Given:
- \(\sin (A) = \frac{4}{5}\) and \(\frac{\pi}{2} < A < \pi\)
- \(\sin (B) = \frac{-2 \sqrt{5}}{5}\) and \(\pi < B < \frac{3 \pi}{2}\)
Let's work through this step-by-step:
### Step 1: Determine \(\cos(A)\)
Since \(\frac{\pi}{2} < A < \pi\), angle \(A\) is in the second quadrant, where sine is positive and cosine is negative. We use the Pythagorean identity:
[tex]\[ \sin^2(A) + \cos^2(A) = 1 \][/tex]
Substituting the given value of \(\sin(A)\):
[tex]\[ \left(\frac{4}{5}\right)^2 + \cos^2(A) = 1 \][/tex]
[tex]\[ \frac{16}{25} + \cos^2(A) = 1 \][/tex]
[tex]\[ \cos^2(A) = 1 - \frac{16}{25} \][/tex]
[tex]\[ \cos^2(A) = \frac{25}{25} - \frac{16}{25} \][/tex]
[tex]\[ \cos^2(A) = \frac{9}{25} \][/tex]
[tex]\[ \cos(A) = \pm \frac{3}{5} \][/tex]
Since \(A\) is in the second quadrant, \(\cos(A)\) is negative:
[tex]\[ \cos(A) = -\frac{3}{5} \][/tex]
### Step 2: Determine \(\cos(B)\)
Since \(\pi < B < \frac{3 \pi}{2}\), angle \(B\) is in the third quadrant where both sine and cosine are negative. Again, we use the Pythagorean identity:
[tex]\[ \sin^2(B) + \cos^2(B) = 1 \][/tex]
Substituting the given value of \(\sin(B)\):
[tex]\[ \left(\frac{-2 \sqrt{5}}{5}\right)^2 + \cos^2(B) = 1 \][/tex]
[tex]\[ \frac{4 \cdot 5}{25} + \cos^2(B) = 1 \][/tex]
[tex]\[ \frac{20}{25} + \cos^2(B) = 1 \][/tex]
[tex]\[ \cos^2(B) = 1 - \frac{20}{25} \][/tex]
[tex]\[ \cos^2(B) = \frac{25}{25} - \frac{20}{25} \][/tex]
[tex]\[ \cos^2(B) = \frac{5}{25} \][/tex]
[tex]\[ \cos(B) = \pm \frac{\sqrt{5}}{5} \][/tex]
Since \(B\) is in the third quadrant, \(\cos(B)\) is negative:
[tex]\[ \cos(B) = -\frac{\sqrt{5}}{5} \][/tex]
### Step 3: Calculate \(\cos(A - B)\)
Now, we use the formula for \(\cos(A - B)\):
[tex]\[ \cos(A - B) = \cos(A)\cos(B) + \sin(A)\sin(B) \][/tex]
Substitute the known values:
[tex]\[ \cos(A - B) = \left(-\frac{3}{5}\right)\left(-\frac{\sqrt{5}}{5}\right) + \left(\frac{4}{5}\right)\left(\frac{-2 \sqrt{5}}{5}\right) \][/tex]
[tex]\[ \cos(A - B) = \frac{3 \sqrt{5}}{25} + \frac{-8 \sqrt{5}}{25} \][/tex]
[tex]\[ \cos(A - B) = \frac{3 \sqrt{5} - 8 \sqrt{5}}{25} \][/tex]
[tex]\[ \cos(A - B) = \frac{-5 \sqrt{5}}{25} \][/tex]
[tex]\[ \cos(A - B) = -\frac{\sqrt{5}}{5} \][/tex]
Thus, the value of \(\cos(A - B)\) is \(-\frac{\sqrt{5}}{5}\).
So, the correct answer is:
[tex]\[ \boxed{-\frac{\sqrt{5}}{5}} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.